A surfactant type drag reducer and a method of preparing the same
Patent Information
- Application Number
- CN202611081244.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-21
- Publication Date
- 2026-10-23
AI Technical Summary
[0003]现有表面活性剂型减阻剂的制备方法通常采用单一表面活性剂组分或简单复配体系,制备过程多为一次性混合溶解后直接稀释使用,此类方法存在一个主要技术缺陷:单一表面活性剂或简单复配体系在流体中形成的胶束结构较为松散,在较高流速和剪切应力条件下,胶束网络容易发生不可逆破坏,导致减阻率显著下降,即便部分现有技术采用阳离子表面活性剂与有机盐复配的方式试图增强胶束强度,但由于未对制备过程中胶束形成与演化的关键阶段进行有效控制,所得减阻剂的抗剪切性能和减阻稳定性仍有待进一步提升
[0042]1、本发明通过阳离子表面活性剂季铵头基与阴离子表面活性剂磺酸根头基之间的静电吸引构建具有交联节点结构的混合胶束前驱体体系,使后续离子诱导胶束生长具有明确的成核位点和定向延伸基础,相较于单一表面活性剂体系或简单复配体系,本发明所得减阻剂形成的动态交联网络骨架具有更高的结构规整度和力学稳定性。
Smart Images

Figure CN122959006A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of fluid drag reduction technology, specifically to a surfactant-type drag reducer and its preparation method. Background Technology
[0002] In oil extraction, gathering and transportation pipelines, and industrial circulating water systems, the frictional resistance generated when fluids flow in pipelines leads to a significant energy loss, reduces transportation efficiency, and increases operating costs. Adding drag-reducing agents is currently one of the main methods to reduce the flow resistance of fluid pipelines. Surfactant-type drag-reducing agents, because they can form micelle systems with specific microstructures under turbulent conditions, effectively reduce fluid turbulent friction. They also have advantages such as good shear recovery and no corrosion to the pipe wall, and have become a research focus in the field of drag reduction technology.
[0003] Existing methods for preparing surfactant-based drag reducers typically employ a single surfactant component or a simple compound system. The preparation process often involves a one-time mixing and dissolution followed by direct dilution for use. This approach has a major technical drawback: the micelle structure formed by a single surfactant or simple compound system in a fluid is relatively loose. Under high flow rates and shear stress conditions, the micelle network is prone to irreversible damage, leading to a significant decrease in drag reduction efficiency. Even though some existing technologies attempt to enhance micelle strength by combining cationic surfactants with organic salts, the shear resistance and drag reduction stability of the resulting drag reducers still need further improvement due to the lack of effective control over the key stages of micelle formation and evolution during the preparation process. Summary of the Invention
[0004] The purpose of this invention is to provide a surfactant-type drag reducer and its preparation method to solve the problems mentioned in the background art.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing a surfactant-type drag-reducing agent, comprising the following steps:
[0006] S1: Disperse the surfactant raw material in deionized water and stir at 200 rpm to 600 rpm for 20 min to 40 min at 40℃ to 60℃ to completely dissolve the surfactant raw material and form a homogeneous surfactant base liquid; The surfactant raw material is a compound system of quaternary ammonium salt cationic surfactant and sulfonate anionic surfactant with a mass ratio of 1:0.3 to 1:4. The quaternary ammonium cationic head group and the sulfonate anionic head group form an ion pair association structure through electrostatic attraction. The ion pair association structure serves as a crosslinking node to construct a mixed micelle precursor system;
[0007] S2: Add water-soluble inorganic salt stabilizer to the homogeneous surfactant base solution and stir at 300 rpm to 800 rpm for 10 min to 25 min at 40℃ to 60℃ until completely dissolved; the mass ratio of water-soluble inorganic salt to surfactant raw material is 0.5:100 to 10:100; the inorganic counterions generated by the ionization of water-soluble inorganic salt replace the original paired counterions of the surfactant ion head group, causing the mixed micelle precursor system to elongate axially and entangle with each other, thus constructing a composite drag-reducing mother liquor system with dynamic cross-linked network skeleton characteristics;
[0008] S3: Cool the composite drag-reducing mother liquor to 25℃~35℃ at 0.5℃ / min~2℃ / min, add a pH adjuster to adjust the pH value to 6.5~8.0, and stir at 400rpm~1000rpm for 5min~15min to obtain a stabilized composite drag-reducing liquid.
[0009] S4: Place the stabilized composite drag-reducing liquid in a sealed container and allow it to stand and cool at room temperature for 60 min to 180 min to obtain the drag-reducing liquid after standing and cooling.
[0010] S5: The drag-reducing liquid after static cooling is subjected to vacuum degassing treatment. The degassing temperature is 25℃~35℃, the vacuum degree is -0.06MPa~-0.09MPa, and the degassing time is 15min~30min to obtain the drag-reducing liquid after degassing treatment.
[0011] S6: Purge nitrogen gas to atmospheric pressure into the deaerator-treated drag-reducing liquid to maintain a nitrogen protective atmosphere. First, add deionized water at a volume of 1 to 5 times that of the stabilized composite drag-reducing liquid for preliminary dilution, and stir at 100 rpm to 300 rpm for 5 to 10 minutes. After the preliminary dilution is completed, add the remaining deionized water for complete dilution, so that the total volume of deionized water for dilution is 10 to 800 times that of the stabilized composite drag-reducing liquid. Stir at 100 rpm to 300 rpm for 15 to 35 minutes to obtain the diluted drag-reducing agent solution.
[0012] S7: Allow the diluted drag-reducing agent solution to stand and age at room temperature for 120 min to 240 min; after standing and aging, stir at a stirring rate of 100 rpm to 300 rpm for 10 min to 20 min; after stirring, perform filtration using a microporous membrane with a pore size of 0.22 μm to 0.45 μm, at a filtration pressure of 0.1 MPa to 0.3 MPa, and at a filtration rate of 50 mL / min to 200 mL / min to obtain the surfactant-type drag-reducing agent.
[0013] As a preferred embodiment of the present invention, step S1 further includes the operation of in-situ construction of auxiliary drag-reducing microparticles, which includes the following steps:
[0014] Soluble zinc salt and soluble aluminum salt are dissolved in deionized water at a zinc-aluminum molar ratio of 2:1 to 4:1 to obtain a mixed salt solution;
[0015] The mixed salt solution was stirred at a stirring rate of 200 rpm to 400 rpm for 10 min to 20 min at room temperature to obtain a uniformly dispersed metal salt precursor solution.
[0016] After the surfactant raw material is completely dissolved in step S1, an alkaline solution is added to the homogeneous surfactant base solution to adjust the pH value of the homogeneous surfactant base solution to 8.0-10.0. Then, the metal salt precursor solution is added dropwise to the homogeneous surfactant base solution at a uniform rate of 5 min-15 min. During the dropwise addition, the temperature of the homogeneous surfactant base solution is maintained at 40℃-60℃. The solution is stirred continuously at a stirring rate of 500 rpm-800 rpm for 30 min-60 min, so that the zinc ions and aluminum ions in the metal salt precursor solution undergo a co-precipitation reaction in the alkaline environment to generate a layered bimetallic hydroxide nanosheet structure.
[0017] In step S2, when a water-soluble inorganic salt stabilizer is added to the homogeneous surfactant base solution, the layered bimetallic hydroxide nanosheet structure is dispersed in the homogeneous surfactant base solution and is simultaneously distributed in the composite drag-reducing mother liquor along with the addition of the stabilizer component.
[0018] As a preferred embodiment of the present invention, the soluble zinc salt is selected from at least one of zinc nitrate, zinc chloride, and zinc sulfate, and the soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate.
[0019] The alkaline solution is selected from sodium hydroxide aqueous solution or potassium hydroxide aqueous solution, and the mass percentage concentration of the alkaline solution is 5% to 15%.
[0020] The total concentration of zinc and aluminum ions in the mixed salt solution was 0.1 mol / L to 1.0 mol / L; the average diameter of the layered bimetallic hydroxide nanosheets was 50 nm to 300 nm, and the average thickness was 5 nm to 20 nm.
[0021] As a preferred technical solution of the present invention, in step S1, the quaternary ammonium salt cationic surfactant and the sulfonate anionic surfactant are dissolved separately in two parts of deionized water, and stirred at a stirring rate of 200 rpm to 600 rpm for 15 min to 30 min respectively under the temperature of 40℃ to 60℃ to obtain the cationic surfactant aqueous solution and the anionic surfactant aqueous solution.
[0022] Then, the cationic surfactant aqueous solution was added dropwise to the anionic surfactant aqueous solution at a uniform rate over 10 min to 20 min. During the dropwise addition, the temperature was maintained at 40℃ to 60℃, and the mixture was stirred continuously at a stirring rate of 300 rpm to 500 rpm for 20 min to 40 min to obtain a homogeneous surfactant base solution.
[0023] As a preferred embodiment of the present invention, in step S2, the water-soluble inorganic salt stabilizer is first prepared as a stabilizer aqueous solution with a mass percentage concentration of 5% to 20% before being added to the homogeneous surfactant base solution, and then uniformly added dropwise to the homogeneous surfactant base solution within 10 min to 20 min; after the dropwise addition is completed, the temperature is maintained at 40℃ to 60℃, and stirring is continued at a stirring rate of 300 rpm to 800 rpm for 10 min to 25 min to completely dissolve the stabilizer components and obtain a composite drag-reducing mother liquor.
[0024] As a preferred technical solution of the present invention, in step S3, after the composite drag-reducing mother liquor is cooled to 25°C to 35°C, it is kept at a constant temperature for 20 min to 40 min.
[0025] After the static heat preservation is completed, stir at a stirring rate of 100 rpm to 300 rpm for 5 min to 10 min to make the internal temperature distribution of the cooled composite drag-reducing mother liquor uniform.
[0026] After stirring, add a pH adjuster to the cooled composite drag-reducing mother liquor. Prepare a pH adjuster aqueous solution with a mass percentage concentration of 1% to 10%, and add it dropwise to the cooled composite drag-reducing mother liquor at a uniform rate over 5 to 15 minutes to adjust the pH value of the cooled composite drag-reducing mother liquor to 7.0 to 7.8.
[0027] During the dropwise addition of the pH regulator aqueous solution, the stirring is continuously carried out at a stirring rate of 200 rpm to 500 rpm. After the pH regulator aqueous solution is added, the stirring rate is adjusted to 400 rpm to 1000 rpm, and stirring is continued for 5 min to 15 min to obtain a stabilized composite drag-reducing liquid.
[0028] As a preferred technical solution of the present invention, in step S4, the stabilized composite drag-reducing liquid is first placed in a sealed container, and then an inert gas is filled into the sealed container. The inert gas is selected from nitrogen or argon, and the pressure inside the sealed container is 0.1MPa to 0.3MPa.
[0029] After the stabilized composite drag-reducing liquid is placed in a sealed container and filled with inert gas, it is continuously rotated and oscillated at a rotation speed of 50 rpm to 150 rpm for 10 min to 30 min.
[0030] After the rotational oscillation is completed, reduce the rotational speed to 10 rpm to 30 rpm and continue the rotational oscillation for 20 min to 40 min.
[0031] After both rotational oscillations are completed, stop the oscillation and transfer the sealed container to a constant temperature environment of 15℃~25℃. Let it stand and cool in the constant temperature environment for 60min~180min. During the standing and cooling process, rotate and oscillate at a rotation rate of 50rpm~100rpm for 5min~10min every 30min.
[0032] After the static cooling is complete, the sealed container is removed from the constant temperature environment and placed in a room temperature environment for 10 to 30 minutes to obtain the drag-reducing liquid after static cooling.
[0033] As a preferred technical solution of the present invention, in step S5, before vacuum degassing, the drag-reducing liquid after standing and cooling is stirred at a stirring rate of 200 rpm to 500 rpm for 5 min to 10 min at a temperature of 25℃ to 35℃.
[0034] After stirring, transfer the drag-reducing liquid that has been allowed to stand and cool to a vacuum degassing container, close all valves of the vacuum degassing container, and start the vacuum pump to reduce the internal pressure of the vacuum degassing container to -0.06MPa to -0.09MPa at a pumping rate of 0.01MPa / min to 0.02MPa / min.
[0035] After the vacuum degree reaches -0.06MPa to -0.09MPa, maintain the vacuum degree for 15min to 30min, and stir for 1min to 2min every 5min at a stirring rate of 100rpm to 200rpm.
[0036] After degassing is completed, air is introduced into the vacuum degassing container at a rate of 0.02 MPa / min to 0.05 MPa / min until atmospheric pressure is reached, thus obtaining the drag-reducing liquid after degassing treatment.
[0037] As a preferred technical solution of the present invention, in step S6, after nitrogen gas is introduced into the drag-reducing liquid after degassing treatment, the nitrogen atmosphere is maintained for 30 min to 60 min, and during the maintenance period, the mixture is continuously stirred at a stirring rate of 50 rpm to 150 rpm.
[0038] During the initial dilution, add deionized water that is 1 to 5 times the volume of the stabilized composite drag-reducing liquid, and stir at 100 rpm to 300 rpm for 5 to 10 minutes.
[0039] After the initial dilution is completed, the remaining deionized water is divided into 3 to 6 equal volumes. Each batch of deionized water is added at a constant rate over 2 to 5 minutes, with a time interval of 3 to 8 minutes between the addition of adjacent batches. After all the deionized water has been added, the mixture is stirred at a stirring rate of 100 to 300 rpm for 15 to 35 minutes to complete the complete dilution operation.
[0040] A surfactant-type drag reducer is prepared by any of the preparation methods described above.
[0041] Compared with the prior art, the beneficial effects of the present invention are:
[0042] 1. This invention constructs a mixed micelle precursor system with cross-linked node structure by electrostatic attraction between the quaternary ammonium head group of the cationic surfactant and the sulfonic acid head group of the anionic surfactant. This provides clear nucleation sites and a basis for directional extension of subsequent ion-induced micelle growth. Compared with single surfactant systems or simple compound systems, the dynamic cross-linked network skeleton formed by the drag-reducing agent obtained in this invention has higher structural regularity and mechanical stability.
[0043] 2. This invention uses inorganic counterions generated by the ionization of water-soluble inorganic salts to replace the original paired counterions of the surfactant ion head base. By controlling the local ionic atmosphere intensity around the ion head base, the mixed micelle precursors are axially elongated and intertwined to form a composite drag-reducing mother liquor system with dynamic cross-linked network skeleton characteristics. This network structure can reversibly dissociate and recombine under shear action, giving the drag-reducing agent excellent shear recovery performance.
[0044] 3. This invention utilizes a synergistic treatment of gradient cooling and pH adjustment to achieve controllable spatial conformational adjustment of the dynamic cross-linked network skeleton in the composite drag-reducing mother liquor system, thereby obtaining a stabilized composite drag-reducing liquid with enhanced structural stability. Combined with vacuum degassing and nitrogen-protected dilution operations, the interference of bubbles and dissolved oxygen in the system on the micelle structure is significantly reduced, further improving the performance consistency and storage stability of the drag-reducing agent product during use. Attached Figure Description
[0045] Figure 1 This is a schematic diagram of the overall process for preparing a surfactant-type drag-reducing agent according to the present invention. Detailed Implementation
[0046] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0047] Example 1
[0048] like Figure 1 As shown, the present invention provides a method for preparing a surfactant-type drag-reducing agent, comprising the following steps:
[0049] S1: Disperse the surfactant raw material in deionized water and stir at 200 rpm to 600 rpm for 20 min to 40 min at 40℃ to 60℃ to completely dissolve the surfactant raw material and form a homogeneous surfactant base liquid; The surfactant raw material is a compound system of quaternary ammonium salt cationic surfactant and sulfonate anionic surfactant with a mass ratio of 1:0.3 to 1:4. The quaternary ammonium cationic head group and the sulfonate anionic head group form an ion pair association structure through electrostatic attraction. The ion pair association structure serves as a crosslinking node to construct a mixed micelle precursor system;
[0050] S2: Add water-soluble inorganic salt stabilizer to the homogeneous surfactant base solution and stir at 300 rpm to 800 rpm for 10 min to 25 min at 40℃ to 60℃ until completely dissolved; the mass ratio of water-soluble inorganic salt to surfactant raw material is 0.5:100 to 10:100; the inorganic counterions generated by the ionization of water-soluble inorganic salt replace the original paired counterions of the surfactant ion head group, causing the mixed micelle precursor system to elongate axially and entangle with each other, thus constructing a composite drag-reducing mother liquor system with dynamic cross-linked network skeleton characteristics;
[0051] S3: Cool the composite drag-reducing mother liquor to 25℃~35℃ at 0.5℃ / min~2℃ / min, add a pH adjuster to adjust the pH value to 6.5~8.0, and stir at 400rpm~1000rpm for 5min~15min to obtain a stabilized composite drag-reducing liquid.
[0052] S4: Place the stabilized composite drag-reducing liquid in a sealed container and allow it to stand and cool at room temperature for 60 min to 180 min to obtain the drag-reducing liquid after standing and cooling.
[0053] S5: The drag-reducing liquid after static cooling is subjected to vacuum degassing treatment. The degassing temperature is 25℃~35℃, the vacuum degree is -0.06MPa~-0.09MPa, and the degassing time is 15min~30min to obtain the drag-reducing liquid after degassing treatment.
[0054] S6: Purge nitrogen gas to atmospheric pressure into the deaerator-treated drag-reducing liquid to maintain a nitrogen protective atmosphere. First, add deionized water at a volume of 1 to 5 times that of the stabilized composite drag-reducing liquid for preliminary dilution, and stir at 100 rpm to 300 rpm for 5 to 10 minutes. After the preliminary dilution is completed, add the remaining deionized water for complete dilution, so that the total volume of deionized water for dilution is 10 to 800 times that of the stabilized composite drag-reducing liquid. Stir at 100 rpm to 300 rpm for 15 to 35 minutes to obtain the diluted drag-reducing agent solution.
[0055] S7: Allow the diluted drag-reducing agent solution to stand and age at room temperature for 120 min to 240 min; after standing and aging, stir at a stirring rate of 100 rpm to 300 rpm for 10 min to 20 min; after stirring, perform filtration using a microporous membrane with a pore size of 0.22 μm to 0.45 μm, at a filtration pressure of 0.1 MPa to 0.3 MPa, and at a filtration rate of 50 mL / min to 200 mL / min to obtain the surfactant-type drag-reducing agent.
[0056] Furthermore, step S1 also includes the operation of in-situ construction of auxiliary drag-reducing particles, which includes the following steps:
[0057] Soluble zinc salt and soluble aluminum salt are dissolved in deionized water at a zinc-aluminum molar ratio of 2:1 to 4:1 to obtain a mixed salt solution;
[0058] The mixed salt solution was stirred at a stirring rate of 200 rpm to 400 rpm for 10 min to 20 min at room temperature to obtain a uniformly dispersed metal salt precursor solution.
[0059] After the surfactant raw material is completely dissolved in step S1, an alkaline solution is added to the homogeneous surfactant base solution to adjust the pH value of the homogeneous surfactant base solution to 8.0-10.0. Then, the metal salt precursor solution is added dropwise to the homogeneous surfactant base solution at a uniform rate of 5 min-15 min. During the dropwise addition, the temperature of the homogeneous surfactant base solution is maintained at 40℃-60℃. The solution is stirred continuously at a stirring rate of 500 rpm-800 rpm for 30 min-60 min, so that the zinc ions and aluminum ions in the metal salt precursor solution undergo a co-precipitation reaction in the alkaline environment to generate a layered bimetallic hydroxide nanosheet structure.
[0060] In step S2, when a water-soluble inorganic salt stabilizer is added to the homogeneous surfactant base solution, the layered bimetallic hydroxide nanosheet structure is dispersed in the homogeneous surfactant base solution and is simultaneously distributed in the composite drag-reducing mother liquor along with the addition of the stabilizer component.
[0061] Furthermore, the soluble zinc salt is selected from at least one of zinc nitrate, zinc chloride, and zinc sulfate, and the soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate;
[0062] The alkaline solution is selected from sodium hydroxide aqueous solution or potassium hydroxide aqueous solution, and the mass percentage concentration of the alkaline solution is 5% to 15%.
[0063] The total concentration of zinc and aluminum ions in the mixed salt solution was 0.1 mol / L to 1.0 mol / L; the average diameter of the layered bimetallic hydroxide nanosheets was 50 nm to 300 nm, and the average thickness was 5 nm to 20 nm.
[0064] Further, in step S1, the quaternary ammonium salt cationic surfactant and the sulfonate anionic surfactant are dissolved separately in two portions of deionized water, and stirred at a stirring rate of 200 rpm to 600 rpm for 15 min to 30 min at a temperature of 40℃ to 60℃ to obtain an aqueous solution of cationic surfactant and an aqueous solution of anionic surfactant.
[0065] Then, the cationic surfactant aqueous solution was added dropwise to the anionic surfactant aqueous solution at a uniform rate over 10 min to 20 min. During the dropwise addition, the temperature was maintained at 40℃ to 60℃, and the mixture was stirred continuously at a stirring rate of 300 rpm to 500 rpm for 20 min to 40 min to obtain a homogeneous surfactant base solution.
[0066] Furthermore, in step S2, before adding the water-soluble inorganic salt stabilizer to the homogeneous surfactant base solution, a stabilizer aqueous solution with a mass percentage concentration of 5% to 20% is first prepared, and then added dropwise to the homogeneous surfactant base solution at a uniform rate over 10 min to 20 min. After the addition is completed, the temperature is maintained at 40℃ to 60℃, and stirring is continued at a stirring rate of 300 rpm to 800 rpm for 10 min to 25 min to completely dissolve the stabilizer components and obtain the composite drag-reducing mother liquor.
[0067] Furthermore, in step S3, after the composite drag-reducing mother liquor is cooled to 25℃~35℃, it is kept at a constant temperature for 20min~40min.
[0068] After the static heat preservation is completed, stir at a stirring rate of 100 rpm to 300 rpm for 5 min to 10 min to make the internal temperature distribution of the cooled composite drag-reducing mother liquor uniform.
[0069] After stirring, add a pH adjuster to the cooled composite drag-reducing mother liquor. Prepare a pH adjuster aqueous solution with a mass percentage concentration of 1% to 10%, and add it dropwise to the cooled composite drag-reducing mother liquor at a uniform rate over 5 to 15 minutes to adjust the pH value of the cooled composite drag-reducing mother liquor to 7.0 to 7.8.
[0070] During the dropwise addition of the pH regulator aqueous solution, the stirring is continuously carried out at a stirring rate of 200 rpm to 500 rpm. After the pH regulator aqueous solution is added, the stirring rate is adjusted to 400 rpm to 1000 rpm, and stirring is continued for 5 min to 15 min to obtain a stabilized composite drag-reducing liquid.
[0071] Furthermore, in step S4, the stabilized composite drag-reducing liquid is first placed in a sealed container, and then an inert gas is filled into the sealed container. The inert gas is selected from nitrogen or argon, and the pressure inside the sealed container is 0.1MPa to 0.3MPa.
[0072] After the stabilized composite drag-reducing liquid is placed in a sealed container and filled with inert gas, it is continuously rotated and oscillated at a rotation speed of 50 rpm to 150 rpm for 10 min to 30 min.
[0073] After the rotational oscillation is completed, reduce the rotational speed to 10 rpm to 30 rpm and continue the rotational oscillation for 20 min to 40 min.
[0074] After both rotational oscillations are completed, stop the oscillation and transfer the sealed container to a constant temperature environment of 15℃~25℃. Let it stand and cool in the constant temperature environment for 60min~180min. During the standing and cooling process, rotate and oscillate at a rotation rate of 50rpm~100rpm for 5min~10min every 30min.
[0075] After the static cooling is complete, the sealed container is removed from the constant temperature environment and placed in a room temperature environment for 10 to 30 minutes to obtain the drag-reducing liquid after static cooling.
[0076] Furthermore, in step S5, before vacuum degassing, the drag-reducing liquid after standing and cooling is stirred at a stirring rate of 200 rpm to 500 rpm for 5 min to 10 min at a temperature of 25℃ to 35℃.
[0077] After stirring, transfer the drag-reducing liquid that has been allowed to stand and cool to a vacuum degassing container, close all valves of the vacuum degassing container, and start the vacuum pump to reduce the internal pressure of the vacuum degassing container to -0.06MPa to -0.09MPa at a pumping rate of 0.01MPa / min to 0.02MPa / min.
[0078] After the vacuum degree reaches -0.06MPa to -0.09MPa, maintain the vacuum degree for 15min to 30min, and stir for 1min to 2min every 5min at a stirring rate of 100rpm to 200rpm.
[0079] After degassing is completed, air is introduced into the vacuum degassing container at a rate of 0.02 MPa / min to 0.05 MPa / min until atmospheric pressure is reached, thus obtaining the drag-reducing liquid after degassing treatment.
[0080] Furthermore, in step S6, after nitrogen gas is introduced into the drag-reducing liquid after degassing treatment, the nitrogen atmosphere is maintained for 30 min to 60 min, and the mixture is continuously stirred at a stirring rate of 50 rpm to 150 rpm during the maintenance period.
[0081] During the initial dilution, add deionized water that is 1 to 5 times the volume of the stabilized composite drag-reducing liquid, and stir at 100 rpm to 300 rpm for 5 to 10 minutes.
[0082] After the initial dilution is completed, the remaining deionized water is divided into 3 to 6 equal volumes. Each batch of deionized water is added at a constant rate over 2 to 5 minutes, with a time interval of 3 to 8 minutes between the addition of adjacent batches. After all the deionized water has been added, the mixture is stirred at a stirring rate of 100 to 300 rpm for 15 to 35 minutes to complete the complete dilution operation.
[0083] A surfactant-type drag reducer is prepared by any of the preparation methods described above.
[0084] Example 2
[0085] Taking the drag reduction application in a gathering and transmission pipeline of an oilfield in eastern China as an example, the performance of the surfactant-type drag reducer of the present invention is verified.
[0086] A compound system of hexadecyltrimethylammonium chloride and sodium dodecyl sulfonate was used as the surfactant raw material at a mass ratio of 1:0.5. Sodium sulfate was used as a stabilizer, added at 2% of the surfactant raw material mass. The surfactant raw material was dispersed in deionized water and stirred at 400 rpm for 30 min at 50 °C to completely dissolve the surfactant raw material, forming a homogeneous surfactant base solution. Sodium sulfate was added to the homogeneous surfactant base solution, and the temperature was maintained at 50 °C. The solution was stirred at 500 rpm for 15 min until completely dissolved, obtaining a composite drag-reducing mother liquor. The composite drag-reducing mother liquor was cooled to 30 °C at a cooling rate of 1 °C / min, and sodium hydroxide solution was added to adjust the pH to 7.0. The solution was stirred at 600 rpm for 10 min to obtain... The stabilized composite drag-reducing liquid was placed in a sealed container and allowed to cool at room temperature for 120 minutes. The cooled liquid was then subjected to vacuum degassing at 30°C and a vacuum of -0.08 MPa for 20 minutes. Nitrogen gas was then introduced into the degassed liquid to atmospheric pressure to maintain a protective nitrogen atmosphere. Deionized water was added to dilute the liquid, with the volume of deionized water being 100 times the volume of the stabilized composite drag-reducing liquid. The mixture was stirred at 200 rpm for 25 minutes to obtain a surfactant-type drag-reducing agent. After preparation, the obtained drag-reducing agent was diluted to the target concentration to prepare aqueous solutions with mass concentrations of 200 ppm, 400 ppm, 600 ppm, 800 ppm, and 1000 ppm.
[0087] The drag reduction performance of the above-mentioned drag-reducing agent aqueous solutions at various concentrations was tested using a pipeline friction measuring device. The test pipeline was a stainless steel circular pipe with an inner diameter of 25 mm. The test temperature was 40℃, and the test flow rate range was 1 m / s to 5 m / s. The drag reduction rate was calculated according to the following formula:
[0088] DR = (ΔP0 - ΔP) / ΔP0 × 100%
[0089] In the above formula, DR is the drag reduction rate, ΔP0 is the pressure drop of pure water, and ΔP is the pressure drop of the drag-reducing agent solution.
[0090] The drag reduction rate test results of drag-reducing agent aqueous solutions of various concentrations at different flow rates are shown in Table 1.
[0091] Table 1 shows the drag reduction rates of drag-reducing agent solutions of different concentrations at different flow rates.
[0092] Flow velocity (m / s) 200ppm drag reduction rate (%) 400ppm drag reduction rate (%) 600ppm drag reduction rate (%) 800ppm drag reduction rate (%) Drag reduction rate (%) at 1000 ppm 1.0 28.6 35.2 42.7 48.3 52.1 1.5 32.4 40.8 49.6 55.7 59.3 2.0 35.7 45.1 54.3 61.2 65.8 2.5 38.2 48.6 58.7 65.9 70.2 3.0 39.5 50.3 61.5 68.8 73.6 3.5 40.1 51.2 63.4 70.5 75.1 4.0 38.8 50.7 62.8 69.6 74.3 4.5 36.5 48.9 60.5 67.2 72.1 5.0 33.2 45.6 57.3 63.8 68.5
[0093] As shown in Table 1, the drag reduction rate increases with the increase of the drag-reducing agent's mass concentration. When the drag-reducing agent's mass concentration is 1000 ppm and the flow rate is 3.5 m / s, the drag reduction rate reaches its maximum value of 75.1%. Under the same mass concentration conditions, the drag reduction rate shows a trend of first increasing and then decreasing with the increase of flow rate, indicating that there is an optimal drag-reducing flow rate range for the drag-reducing agent aqueous solution. For the drag-reducing agent aqueous solution with a mass concentration of 600 ppm, the drag reduction rate remains above 58% in the flow rate range of 2.5 m / s to 4.5 m / s, indicating that the drag-reducing agent of the present invention has stable drag-reducing performance in a wide flow rate range.
[0094] To further test the shear recovery performance of the drag-reducing agent aqueous solution, a 1000 ppm drag-reducing agent aqueous solution was circulated in the test pipeline for 120 min, and samples were taken every 30 min to measure the drag reduction rate at a flow rate of 3.5 m / s. The results are shown in Table 2.
[0095] Table 2 shows the drag reduction rate after circulating a 1000ppm drag-reducing agent aqueous solution for different times.
[0096] Cycle time (min) 0 30 60 90 120 Drag reduction rate (%) 75.1 73.8 72.9 73.2 72.5
[0097] As shown in Table 2, after 120 minutes of circulating flow, the drag reduction rate decreased from the initial value of 75.1% to 72.5%, a decrease of 2.6 percentage points, indicating that the surfactant-type drag reducer of the present invention has good shear resistance and shear recovery properties.
[0098] Taking a high-temperature gathering and transmission pipeline in an oilfield in western China as an example, the drag reduction performance of the drag reduction agent of the present invention under high-temperature conditions was tested. An 800ppm drag reduction agent aqueous solution was used to measure the drag reduction rate at a flow rate of 3.5m / s under temperature conditions of 30℃, 40℃, 50℃, 60℃, 70℃ and 80℃ respectively. The results are shown in Table 3.
[0099] Table 3 shows the drag reduction rate of 800 ppm drag-reducing agent aqueous solution at different temperatures.
[0100] Temperature (°C) 30 40 50 60 70 80 Drag reduction rate (%) 72.8 73.4 74.1 73.6 71.2 67.8
[0101] As shown in Table 3, the drag reduction rate of the drag-reducing agent aqueous solution of the present invention remains above 71% in the temperature range of 30℃ to 70℃, indicating that the drag-reducing agent has good temperature resistance and is suitable for fluid transportation pipelines under different temperature conditions.
[0102] Example 3
[0103] Taking the drag reduction and energy-saving renovation of the circulating water system of a petrochemical enterprise in China as an example, the application effect of the surfactant-type drag reducer of the present invention is evaluated.
[0104] A compound system of octadecyltrimethylammonium chloride and sodium dodecylbenzenesulfonate was used as the surfactant raw material in a mass ratio of 1:1. Sodium salicylate was used as a stabilizer, added at 3% of the surfactant raw material mass. The surfactant raw material was dispersed in deionized water and stirred at 400 rpm for 30 min at 50 °C to completely dissolve the surfactant raw material, forming a homogeneous surfactant base solution. Sodium salicylate was added to the homogeneous surfactant base solution, and the temperature was maintained at 50 °C. The solution was stirred at 500 rpm for 15 min until completely dissolved, obtaining a composite drag-reducing mother liquor. The composite drag-reducing mother liquor was cooled to 30 °C at a cooling rate of 1 °C / min, and sodium hydroxide solution was added to adjust the pH to 7.5. The solution was stirred at 600 rpm for 10 min. n. To obtain a stabilized composite drag-reducing liquid, place the stabilized composite drag-reducing liquid in a sealed container and allow it to stand and cool at room temperature for 120 min. Perform vacuum degassing treatment on the cooled drag-reducing liquid at a degassing temperature of 30℃, a vacuum degree of -0.08MPa, and a degassing time of 20 min. Purge the drag-reducing liquid with nitrogen gas to atmospheric pressure to maintain a nitrogen protective atmosphere. Add deionized water to dilute the liquid, with the volume of deionized water being 100 times the volume of the stabilized composite drag-reducing liquid. Stir at 200 rpm for 25 min to obtain a surfactant-type drag-reducing agent. After preparation, dilute the obtained drag-reducing agent to the target concentration and prepare drag-reducing agent aqueous solutions with mass concentrations of 300 ppm, 500 ppm, 700 ppm, and 900 ppm, respectively.
[0105] The drag reduction performance was evaluated using a circulating pipeline friction test device. The test tube was an organic glass tube with an inner diameter of 50 mm. The test temperature was 50℃, and the test flow rate range was 0.5 m / s to 4.0 m / s. The drag reduction rate test results of drag-reducing agent aqueous solutions of various concentrations at different flow rates are shown in Table 4.
[0106] Table 4 shows the drag reduction rates of drag-reducing agent solutions of different concentrations at different flow rates.
[0107] Flow velocity (m / s) 300ppm drag reduction rate (%) 500ppm drag reduction rate (%) 700ppm drag reduction rate (%) 900ppm drag reduction rate (%) 0.5 22.3 29.8 36.5 42.1 1.0 30.5 40.2 48.7 55.3 1.5 36.2 47.8 57.4 64.6 2.0 40.5 53.6 64.2 72.8 2.5 42.8 56.9 68.5 77.3 3.0 44.1 58.7 70.8 79.5 3.5 43.6 57.5 69.2 78.1 4.0 40.8 54.3 65.7 74.6
[0108] As shown in Table 4, the drag reduction rate of the 900 ppm drag-reducing agent aqueous solution reached 79.5% at a flow rate of 3.0 m / s, which is significantly higher than the drag reduction effect under low concentration conditions. The drag reduction rate of the 700 ppm drag-reducing agent aqueous solution exceeded 68% in the flow rate range of 2.5 m / s to 3.5 m / s, indicating that the drag-reducing agent performs well in a wide range of concentrations and flow rates.
[0109] The drag reduction performance stability of the drag-reducing agent aqueous solution under different pH conditions was tested. A 900 ppm drag-reducing agent aqueous solution was used, and the pH value was adjusted to 5.5, 6.0, 6.5, 7.0, 7.5, 8.0 and 8.5 with hydrochloric acid and sodium hydroxide solution, respectively. The drag reduction rate was measured at a flow rate of 3.0 m / s and 50℃. The results are shown in Table 5.
[0110] Table 5 shows the drag reduction rate of a 900ppm drag-reducing agent aqueous solution at different pH values.
[0111] pH value 5.5 6.0 6.5 7.0 7.5 8.0 8.5 Drag reduction rate (%) 68.2 72.5 76.8 79.5 80.1 79.2 75.6
[0112] As shown in Table 5, the drag reduction rate of the drag-reducing agent aqueous solution of the present invention remains above 76% in the pH range of 6.5 to 8.0, and exceeds 79% in the pH range of 7.0 to 8.0. This indicates that the drag-reducing agent has stable drag reduction performance over a wide pH range and is suitable for pipeline systems with different water quality conditions.
[0113] The drag reduction durability of the drag-reducing agent aqueous solution during the circulating flow process was tested. A 900 ppm drag-reducing agent aqueous solution was continuously circulated in the test pipeline for 240 min. Samples were taken every 60 min to measure the drag reduction rate at a flow rate of 3.0 m / s. The results are shown in Table 6.
[0114] Table 6 shows the drag reduction rate after continuous circulation of a 900ppm drag-reducing agent aqueous solution for different times.
[0115] Running time (min) 0 60 120 180 240 Drag reduction rate (%) 79.5 78.9 78.1 77.3 76.6
[0116] As shown in Table 6, after 240 minutes of continuous operation, the drag reduction rate decreased from the initial value of 79.5% to 76.6%, a decrease of 2.9 percentage points. This indicates that the drag reduction agent of the present invention has excellent drag reduction durability and is suitable for pipeline systems with long-term operation.
[0117] Taking an industrial circulating water pipeline system in a coastal area of eastern China as an example, a field application test was conducted using the drag-reducing agent of this invention. The pipeline system has a diameter of 300 mm, transports circulating cooling water, and the water temperature is 45℃ to 55℃. The drag-reducing agent concentration is 700 ppm. The system operated continuously for 360 hours. During the operation, pressure drop data at the pipeline inlet and outlet were collected every 72 hours, and the drag reduction rate was calculated. Before operation, the pipeline pressure drop was 0.85 MPa. After adding the drag-reducing agent, the pressure drop decreased to 0.28 MPa, corresponding to a drag reduction rate of 67.1%. After 360 hours of operation, the pressure drop was 0.31 MPa, corresponding to a drag reduction rate of 63.5%. The field application test results show that the surfactant-type drag-reducing agent of this invention can still maintain a high drag reduction efficiency under long-term operating conditions, with a drag reduction rate retention rate exceeding 94%.
[0118] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention.
Claims
1. A method for preparing a surfactant-type drag-reducing agent, characterized in that, Includes the following steps: S1: Disperse the surfactant raw material in deionized water and stir at 200 rpm to 600 rpm for 20 min to 40 min at 40℃ to 60℃ to completely dissolve the surfactant raw material and form a homogeneous surfactant base liquid; The surfactant raw material is a compound system of quaternary ammonium salt cationic surfactant and sulfonate anionic surfactant with a mass ratio of 1:0.3 to 1:
4. The quaternary ammonium cationic head group and the sulfonate anionic head group form an ion pair association structure through electrostatic attraction. The ion pair association structure serves as a crosslinking node to construct a mixed micelle precursor system; S2: Add water-soluble inorganic salt stabilizer to the homogeneous surfactant base solution and stir at 300 rpm to 800 rpm for 10 min to 25 min at 40℃ to 60℃ until completely dissolved; the mass ratio of water-soluble inorganic salt to surfactant raw material is 0.5:100 to 10:100; the inorganic counterions generated by the ionization of water-soluble inorganic salt replace the original paired counterions of the surfactant ion head group, causing the mixed micelle precursor system to elongate axially and entangle with each other, thus constructing a composite drag-reducing mother liquor system with dynamic cross-linked network skeleton characteristics; S3: Cool the composite drag-reducing mother liquor to 25℃~35℃ at 0.5℃ / min~2℃ / min, add a pH adjuster to adjust the pH value to 6.5~8.0, and stir at 400rpm~1000rpm for 5min~15min to obtain a stabilized composite drag-reducing solution. S4: Place the stabilized composite drag-reducing liquid in a sealed container and allow it to stand and cool at room temperature for 60 min to 180 min to obtain the drag-reducing liquid after standing and cooling. S5: The drag-reducing liquid after static cooling is subjected to vacuum degassing treatment. The degassing temperature is 25℃~35℃, the vacuum degree is -0.06MPa~-0.09MPa, and the degassing time is 15min~30min to obtain the drag-reducing liquid after degassing treatment. S6: Purge nitrogen gas to atmospheric pressure into the deaerator-treated drag-reducing liquid to maintain a nitrogen protective atmosphere. First, add deionized water at a volume of 1 to 5 times that of the stabilized composite drag-reducing liquid for preliminary dilution, and stir at 100 rpm to 300 rpm for 5 to 10 minutes. After the preliminary dilution is completed, add the remaining deionized water for complete dilution, so that the total volume of deionized water for dilution is 10 to 800 times that of the stabilized composite drag-reducing liquid. Stir at 100 rpm to 300 rpm for 15 to 35 minutes to obtain the diluted drag-reducing agent solution. S7: Allow the diluted drag-reducing agent solution to stand and age at room temperature for 120 min to 240 min; after standing and aging, stir at a stirring rate of 100 rpm to 300 rpm for 10 min to 20 min; after stirring, perform filtration using a microporous membrane with a pore size of 0.22 μm to 0.45 μm, at a filtration pressure of 0.1 MPa to 0.3 MPa, and at a filtration rate of 50 mL / min to 200 mL / min to obtain the surfactant-type drag-reducing agent.
2. The preparation method according to claim 1, characterized in that, Step S1 further includes the operation of in-situ construction of auxiliary drag-reducing microparticles, which includes the following steps: Soluble zinc salt and soluble aluminum salt are dissolved in deionized water at a zinc-aluminum molar ratio of 2:1 to 4:1 to obtain a mixed salt solution. The mixed salt solution was stirred at a stirring rate of 200 rpm to 400 rpm for 10 min to 20 min at room temperature to obtain a uniformly dispersed metal salt precursor solution. After the surfactant raw material is completely dissolved in step S1, an alkaline solution is added to the homogeneous surfactant base solution to adjust the pH value of the homogeneous surfactant base solution to 8.0-10.
0. Then, the metal salt precursor solution is added dropwise to the homogeneous surfactant base solution at a uniform rate of 5 min-15 min. During the dropwise addition, the temperature of the homogeneous surfactant base solution is maintained at 40℃-60℃. The solution is stirred continuously at a stirring rate of 500 rpm-800 rpm for 30 min-60 min, so that the zinc ions and aluminum ions in the metal salt precursor solution undergo a co-precipitation reaction in the alkaline environment to generate a layered bimetallic hydroxide nanosheet structure. In step S2, when a water-soluble inorganic salt stabilizer is added to the homogeneous surfactant base solution, the layered bimetallic hydroxide nanosheet structure is dispersed in the homogeneous surfactant base solution and is simultaneously distributed in the composite drag-reducing mother liquor along with the addition of the stabilizer component.
3. The preparation method according to claim 2, characterized in that, The soluble zinc salt is selected from at least one of zinc nitrate, zinc chloride, and zinc sulfate, and the soluble aluminum salt is selected from at least one of aluminum nitrate, aluminum chloride, and aluminum sulfate. The alkaline solution is selected from sodium hydroxide aqueous solution or potassium hydroxide aqueous solution, and the mass percentage concentration of the alkaline solution is 5% to 15%. The total concentration of zinc and aluminum ions in the mixed salt solution was 0.1 mol / L to 1.0 mol / L; the average diameter of the layered bimetallic hydroxide nanosheets was 50 nm to 300 nm, and the average thickness was 5 nm to 20 nm.
4. The preparation method according to claim 1, characterized in that, In step S1, the quaternary ammonium salt cationic surfactant and the sulfonate anionic surfactant are dissolved separately in two portions of deionized water, and stirred at a stirring rate of 200 rpm to 600 rpm for 15 min to 30 min at a temperature of 40℃ to 60℃ to obtain an aqueous solution of cationic surfactant and an aqueous solution of anionic surfactant. Then, the cationic surfactant aqueous solution was added dropwise to the anionic surfactant aqueous solution at a uniform rate over 10 min to 20 min. During the dropwise addition, the temperature was maintained at 40℃ to 60℃, and the mixture was stirred continuously at a stirring rate of 300 rpm to 500 rpm for 20 min to 40 min to obtain a homogeneous surfactant base solution.
5. The preparation method according to claim 1, characterized in that, In step S2, before adding the water-soluble inorganic salt stabilizer to the homogeneous surfactant base solution, a stabilizer aqueous solution with a mass percentage concentration of 5% to 20% is first prepared, and then added dropwise to the homogeneous surfactant base solution at a uniform rate over 10 min to 20 min. After the dropwise addition is completed, the temperature is maintained at 40℃ to 60℃, and stirring is continued at a stirring rate of 300 rpm to 800 rpm for 10 min to 25 min to completely dissolve the stabilizer components and obtain a composite drag-reducing mother liquor.
6. The preparation method according to claim 1, characterized in that, In step S3, after the composite drag-reducing mother liquor is cooled to 25℃~35℃, it is kept at a constant temperature for 20min~40min. After the static heat preservation is completed, stir at a stirring rate of 100 rpm to 300 rpm for 5 min to 10 min to make the internal temperature distribution of the cooled composite drag-reducing mother liquor uniform. After stirring, add a pH adjuster to the cooled composite drag-reducing mother liquor. Prepare a pH adjuster aqueous solution with a mass percentage concentration of 1% to 10%, and add it dropwise to the cooled composite drag-reducing mother liquor at a uniform rate over 5 to 15 minutes to adjust the pH value of the cooled composite drag-reducing mother liquor to 7.0 to 7.
8. During the dropwise addition of the pH regulator aqueous solution, the stirring is continuously carried out at a stirring rate of 200 rpm to 500 rpm. After the pH regulator aqueous solution is added, the stirring rate is adjusted to 400 rpm to 1000 rpm, and stirring is continued for 5 min to 15 min to obtain a stabilized composite drag-reducing liquid.
7. The preparation method according to claim 1, characterized in that, In step S4, the stabilized composite drag-reducing liquid is first placed in a sealed container, and then an inert gas is filled into the sealed container. The inert gas is selected from nitrogen or argon, and the pressure inside the sealed container is 0.1MPa to 0.3MPa. After the stabilized composite drag-reducing liquid is placed in a sealed container and filled with inert gas, it is continuously rotated and oscillated at a rotation speed of 50 rpm to 150 rpm for 10 min to 30 min. After the rotational oscillation is completed, reduce the rotational speed to 10 rpm to 30 rpm and continue the rotational oscillation for 20 min to 40 min. After both rotational oscillations are completed, stop the oscillation and transfer the sealed container to a constant temperature environment of 15℃~25℃. Let it stand and cool in the constant temperature environment for 60min~180min. During the standing and cooling process, rotate and oscillate at a rotation rate of 50rpm~100rpm for 5min~10min every 30min. After the static cooling is complete, the sealed container is removed from the constant temperature environment and placed in a room temperature environment for 10 to 30 minutes to obtain the drag-reducing liquid after static cooling.
8. The preparation method according to claim 1, characterized in that, In step S5, before vacuum degassing, the drag-reducing liquid that has been allowed to stand and cool is stirred at a stirring rate of 200 rpm to 500 rpm for 5 min to 10 min at a temperature of 25℃ to 35℃. After stirring, transfer the drag-reducing liquid that has been allowed to stand and cool to a vacuum degassing container, close all valves of the vacuum degassing container, and start the vacuum pump to reduce the internal pressure of the vacuum degassing container to -0.06MPa to -0.09MPa at a pumping rate of 0.01MPa / min to 0.02MPa / min. After the vacuum degree reaches -0.06MPa to -0.09MPa, maintain the vacuum degree for 15min to 30min, and stir for 1min to 2min every 5min at a stirring rate of 100rpm to 200rpm. After degassing is completed, air is introduced into the vacuum degassing container at a rate of 0.02 MPa / min to 0.05 MPa / min until atmospheric pressure is reached, thus obtaining the drag-reducing liquid after degassing treatment.
9. The preparation method according to claim 1, characterized in that, In step S6, after nitrogen gas is introduced into the drag-reducing liquid after degassing treatment, the nitrogen atmosphere is maintained for 30 min to 60 min, and the mixture is continuously stirred at a stirring rate of 50 rpm to 150 rpm during the maintenance period. During the initial dilution, add deionized water that is 1 to 5 times the volume of the stabilized composite drag-reducing liquid, and stir at 100 rpm to 300 rpm for 5 to 10 minutes. After the initial dilution is completed, the remaining deionized water is divided into 3 to 6 equal volumes. Each batch of deionized water is added at a constant rate over 2 to 5 minutes, with a time interval of 3 to 8 minutes between the addition of adjacent batches. After all the deionized water has been added, the mixture is stirred at a stirring rate of 100 to 300 rpm for 15 to 35 minutes to complete the complete dilution operation.
10. A surfactant-type drag reducer, characterized in that, It is prepared by the preparation method described in any one of claims 1-9.